Project failure Indicators: perceptions of Thai and Malaysian engineers - Pittayaporn Gomarn; Jakrapong Pongpeng (My University, 2018)
This research aims to compare the rank and importance level of failure indicators of the construction projects from the perception of Thai and Malaysian engineers. The questionnaire was used to survey the opinions of the engineers who supervised construction projects in Bangkok, Thailand and Kuala Lumpur, Malaysia. Analysis of the data was undertaken with the use of SPSS software which included a comparison of the importance level of construction project failure indicators from the perception of Thai and Malaysian engineers. Additionally, the Mann Whitney U test was used to compare the similarities and differences of construction project failure indicators from the perceptions of both Thai and Malaysian engineers. The results showed that construction project failure indicators from both Thai and Malaysian engineers were similar. Failure indicators ranked in importance were: 1) negative effects on safety, health and environment (18.83%), 2) cost overrun (18.44%), 3) time overruns (17.41%), 4) quality defects (16.43%), 5) stakeholders' dissatisfaction (15.36%), and 6) dispute and litigation (13.54%). The outcome of the research is therefore useful in assisting supervisory staff better understand project failure indicators. In addition, the research can be used as a guideline for analyzing the risk of failures in construction projects.
Keywords: Questionnaire; Construction Project Management and Performance